Control of THz Surface Plasmons by Geometric Phases - Hu, Shulin; Wang, Peng; Zhou, Cai; Hu, Min; Xiong, Yuli; Xu, Huanhuan; Li, Xiaoyu; Xu, Mingyao; Wang, Shengxiang (Frontiers in Physics, 2021)
Surface plasmons (SPs) promise versatile potential applications in many aspects and thus have been a subject of enormous interest. However, most of the previous studies are mainly realized the manipulation of SPs by designing the structure of the individual meta-atom. Seeking new approaches in SW control is highly desired in developing next-generation integrated photonic devices and components, which enable to realize more diverse modulation and higher efficiency. Here, a systematic study of tunable emission of SP with metasurface, which acts as an on-chip plasmonic vortices (PVs) source, is presented. Meanwhile, to verify the controllability of the directional excitation of SP, we have designed beam deflectors with different angles of surface wave (SW). Furthermore, PVs with different topological charges can also be generated by arranging the spatially-varied nanoslits. The proposed controlling strategy offers a versatile platform for a variety of promising applications, such as propagating control of SPs and PVs generation on-chip.